Infrahepatic inferior vena cava clamping does not increase the risk of pulmonary embolism following hepatic resection - Birgin, Emrullah; Mehrabi, Arianeb; Sturm, Dorothée; Reißfelder, Christoph; Weitz, Jürgen; Rahbari, Nuh Nabi (World journal of surgery, 2021)
Infrahepatic inferior vena cava (IVC) clamping reduces central venous pressure. However, controversies remain regarding its impact on postoperative complications, particularly, the incidence of postoperative pulmonary embolism (PE). The aim of the study was to determine the impact of IVC clamping on the incidence of PE in patients undergoing hepatectomy.
Gesehen am 14.12.2022